CLINICAL AND LABORATORY FEATURES OF ENDOGENOUS INTOXICATION SYNDROME IN CHILDREN UNDER 3 YEARS WITH PNEUMONIA - R.M. ABDURAKHIMOV; A. VOKHIDOV (Паёми Сино, 2020)
Objective: To study the clinical features of the course and the dynamics of some haematological indices in endogenous intoxication syndrome in children under 3 years of age suffering from pneumonia.